From Forced Confessions to Digital Coercion: Rethinking the Admissibility of Evidence in Criminal Trials in Indonesia - Kasim, Ramdhan (Faculty of Law, Universitas Pasundan, 2025)
The Indonesian criminal justice system still accepts evidence obtained through coercion, either physical or digital, because there is no principle-based exclusion framework and the courts don't have enough control. This absence of normative guidance violates both the constitutional assurance of due process and the enforceable obligations under international human rights law. The objective of this research is to examine Indonesia's evidentiary doctrine and formulate a strategy for the exclusion of illegally obtained evidence from a rights-based standpoint. This research utilizes a normative juridical methodology, incorporating literature reviews, comparative law, and statutory analysis. The findings indicate that Indonesian courts are grossly unprepared to address modern forms of coercion, including those facilitated by algorithmic manipulation and digital surveillance. You can see where Indonesia is falling short by looking at how the US, Germany, and the European Court of Human Rights have done things in the past. This study introduces digital coercion as a novel analytical category and contends that evidence obtained through digital means undermines the legitimacy of adjudication and the voluntariness of the process. The study's prescriptive contribution advocates for the establishment of pre-trial evidentiary hearings, the integration of a definitive exclusionary rule into KUHAP, and the formulation of procedural safeguards for digital evidence. This study offers a robust foundation for reevaluating Indonesia's evidence doctrine in consideration of the ethical dilemmas presented by contemporary criminal justice and in accordance with international standards.